PENGEMBANGAN KONTEN E-LEARNING MATAKULIAH MEDIA DAN SUMBER BELAJAR BERBASIS PROBLEM BASED LEARNING - Muhammad Ragil Kurniawan; Nurul Hidayati Rofiah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study intends to develop the potential of digital-based learning resources. This research aims to: a) Knowing the process of developing E-learning content course of Media and Learning Resources based on Problem Based Learning, b) Knowing the appropriateness of E-learning content course of Media and Learning Resources based on Problem Based Learning. This research is research and development. The object of this research is media and learning resources course based on problem based learning. The data collection method used was an assessment sheet, supported by the results of interviews with education experts and practitioners. The data in this study are the results of assessments from experts. The results of the research data were processed using descriptive statistical data. The results are: a) E-learning content development procedures through four stages: preliminary study, development of learning design, product development and product evaluation. b) Assessment results by material experts is 3,4 (good category), media expert judge by 3,5 (good category), and prospective users judge by 4,3 (very good category).Â Based on the assessment result E-learning quality course of Media and Learning Resources based on problem based learning for learning materials in elementary schools are considered suitable for use as learning resources.Â